Mechanical signals activate p38 MAPK pathway-dependent reinforcement of actin via mechanosensitive HspB1 - Hoffman, Laura; Jensen, Christopher C; Yoshigi, Masaaki; Beckerle, Mary (Molecular biology of the cell, 2017)
Despite the importance of a cell's ability to sense and respond to mechanical force, the molecular mechanisms by which physical cues are converted to cell-instructive chemical information to influence cell behaviors remain to be elucidated. Exposure of cultured fibroblasts to uniaxial cyclic stretch results in an actin stress fiber reinforcement response that stabilizes the actin cytoskeleton. p38 MAPK signaling is activated in response to stretch, and inhibition of p38 MAPK abrogates stretch-induced cytoskeletal reorganization. Here we show that the small heat shock protein HspB1 (hsp25/27) is phosphorylated in stretch-stimulated mouse fibroblasts via a p38 MAPK-dependent mechanism. Phosphorylated HspB1 is recruited to the actin cytoskeleton, displaying prominent accumulation on actin "comet tails" that emanate from focal adhesions in stretch-stimulated cells. Site-directed mutagenesis to block HspB1 phosphorylation inhibits the protein's cytoskeletal recruitment in response to mechanical stimulation. HspB1-null cells, generated by CRISPR/Cas9 nuclease genome editing, display an abrogated stretch-stimulated actin reinforcement response and increased cell migration. HspB1 is recruited to sites of increased traction force in cells geometrically constrained on micropatterned substrates. Our findings elucidate a molecular pathway by which a mechanical signal is transduced via activation of p38 MAPK to influence actin remodeling and cell migration via a zyxin-independent process.